Association of vitamin D serum levels and its common genetic determinants, with severity of liver fibrosis in genotype 1 chronic hepatitis C patients. Issue 7 (25th March 2013) - Petta, S.; Grimaudo, S.; Marco, V. D.; Scazzone, C.; Macaluso, F. S.; Cammà, C.; Cabibi, D.; Pipitone, R.; Craxì, A.
Summary Lower 25‐hydroxyvitamin D [25(OH)D] serum levels have been associated with the severity of liver fibrosis in genotype 1 chronic hepatitis C patients (G1CHC). In addition, a recent genome‐wide study identified genetic variants (rs12785878, near dehydrocholesterol reductase, DHCR7; rs10741657, near CYP2R1; and rs7041, near vitamin D‐binding protein, GC) affecting 25(OH)D serum levels in healthy populations. We aimed to assess the association between vitamin D serum levels and its genetic determinants, with the severity of liver fibrosis. Two hundred and sixty patients with biopsy‐proven G1CHC were consecutively evaluated. The 25(OH)D serum levels were measured by high‐pressure liquid chromatography. All patients were genotyped for DHCR7 rs12785878, CYP2R1 rs10741657 and GC rs7041 single nucleotide polymorphisms. DHCR7 GG genotype (P = 0.003) and the severity of fibrosis (P = 0.03) were independent factors associated with lower 25(OH)D serum levels in multiple linear regression analysis. Interestingly, 53.8% (7/13) of patients with DHCR7 GG genotype had severe liver fibrosis, compared to 27.1% (67/247) of those with DHCR7 TT/TG genotype (P = 0.03). By multivariate logistic regression analysis, severe fibrosis was independently associated with older age (OR, 1.056; 95% CI, 1.023–1.089, P = 0.001), low cholesterol (OR, 0.984; 95% CI, 0.974–0.994, P = 0.002), high triglycerides (OR, 1.008; 95% CI, 1.002–1.015, P = 0.01), low 25(OH)D (OR, 0.958; 95% CI, 0.919–0.999, P = 0.04), DHCR7 GG genotype (OR, 4.222; 95% CI, 1.106–16.120; P = 0.03), moderate–severe steatosis (OR, 2.588; 95% CI, 1.355–4.943; P = 0.004) and moderate–severe necroinflammatory activity (grading) (OR, 2.437; 95% CI, 1.307–4.763; P = 0.001). No associations were found between liver fibrosis and both CYP2R1 and GC genotypes. In patients with G1CHC, GG homozygosis for DHCR7 gene and lower 25(OH)D levels are independently associated with the severity of liver fibrosis.